The role of sexual orientation in perception of emotional vs. sexual infidelity - Hromatko, Ivana; Tadinac, Meri (2013)
Evolutionary psychology provided a fruitful theoretical framework in the field of jealousy research, resulting in an abundance of evidence in support of an evolved sex difference in what causes jealousy. One of the variables yielding a lot of interest in this line of research is sexual orientation: analysis of patterns of sex differences as a function of sexual orientation offers clues for answering various questions about the nature of human mating dynamics. The neurodevelopmental theory suggests that the etiogenesis of sexual orientation is closely connected to the sexual differentiation of the brain. Indeed, it seems that homosexual women are exposed to a greater degree of masculinisation than heterosexual women, but homosexual men turn out to be either over- or under-masculinised, depending on the trait being studied. Thus, the aim of this study was to address some of these issues and explore whether previously well documented sex differences also existed in homosexual and bisexual populations. An online questionnaire was used to collect socio- demographic data, as well as data on sexual orientation, preference for a long- vs. short-term relationship, and a well-known item used in previous research with a hypothetical situation which could provoke either emotional or sexual jealousy. More than 3000 participants (from a wide range of educational, socio-economical and age groups) completed the questionnaire. Women of different sexual orientations showed very subtle differentiation when it comes to the type of infidelity that they find more upsetting, with heterosexual women having the highest rate of emotional jealousy responses (93.5%), followed by bisexual (86.8%) and homosexual (76.8%) women. Contrary to some previous reports, we found no statistically significant differences between males of different sexual orientations in the type of infidelity they found more upsetting (80% of homosexual and 72% of bisexual and heterosexual men reported the emotional infidelity as being more upsetting). What differentiated the participants who reported being more upset by different infidelity scenarios? Heterosexual participants who reported being more upset by the emotional infidelity were older, more educated and had higher income compared to those who reported sexual infidelity as more upsetting, while none of these differences reached statistical significance in homosexuals and bisexuals. The percentage of heterosexual and homosexual (but not bisexual) men who reported being interested in a long-term relationship was higher among those who would be more upset by the emotional infidelity, while in women this preference was not related to the type of infidelity they reported as more upsetting. Therefore, a complex pattern emerged, with the perception of infidelity being related to several socio-demographic variables, but differently among groups of various sexual orientations.
Projekt MZOS
ENG